A study of the artistic techniques of the French writer Pascal Quignard in the context of developing emotional intelligence in high school students - Nurbanu Abueva; Nurbanu Abueva; Yanqiu Wu; Anna Buzelo; Aisulu Dzhanegizova; Aisulu Dzhanegizova; Dulat Karakushev; Bojan Obrenovic (Frontiers in Psychology, 2025)
This study examines how the French writer Pascal Quignard’s creative approach affects high school students’ emotional intelligence (EI). Quignard’s fragmented storytelling, philosophical insights, and concentration on emotional depth might evoke deeper psychological responses. This study combines quantitative empirical evidence based on Trait Emotional Intelligence Questionnaire (TEIQue) scores with qualitative classroom observations and interviews. The study placed high school students into two groups: one that read Quignard’s works, and the other that followed the literary curriculum. This mixed-methods study examined how reading Pascal Quignard’s work affected high school students’ EI in three areas: self-awareness, emotional regulation, and empathy. This study used quantitative and qualitative methods to examine how Quignard’s thoughtful and emotionally complex work affects students’ emotional growth over a semester. Quantitatively, the experimental group showed a significant 12.2-point increase in EI scores (p < 0.001), while the control group exhibited no change. Qualitatively, thematic analysis revealed that students engaging with Quignard’s texts experienced deeper self-reflection, heightened perspective-taking, and increased empathy. Reading and considering Quignard’s philosophical musings and emotional stories may improve students’ social skills, self-awareness, empathy, and emotional regulation. These complementary quantitative and qualitative findings suggest that teaching Quignard to high school students may improve their emotional and social skills. This study adds to the literature’s positive benefits in education by suggesting that sophisticated and emotionally resonant books can help students develop self-awareness and emotional maturity.